1987
DOI: 10.1088/0034-4885/50/5/002
|View full text |Cite
|
Sign up to set email alerts
|

Inertial confinement fusion driven by heavy-ion beams

Abstract: Fundamental concepts, current status and future prospects of heavy-ion-driven inertial confinement fusion are described. Target physics issues are emphasised. An account is given of experimental programmes now under way, including beam/plasma interaction and accelerator physics experiments. Plans for high-intensity beam/target research using heavy-ion beams from the synchrotron at GSI, Darmstadt, FRG are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(39 citation statements)
references
References 115 publications
(52 reference statements)
0
36
0
1
Order By: Relevance
“…This is a remarkable property in the sense that, for instance, a 10-GeV bismuth ion can lose all its energy in a material thickness of less than 0.1 g/cm 2 . As recently shown by the Darmstadt group [Arnold & Meyer-ter-Vehn (1987), for effects of range shortening, see Hofmann et al (1988)], "hot" absorbers further enhance such a property by a factor that can be as much as two or three.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This is a remarkable property in the sense that, for instance, a 10-GeV bismuth ion can lose all its energy in a material thickness of less than 0.1 g/cm 2 . As recently shown by the Darmstadt group [Arnold & Meyer-ter-Vehn (1987), for effects of range shortening, see Hofmann et al (1988)], "hot" absorbers further enhance such a property by a factor that can be as much as two or three.…”
Section: Introductionmentioning
confidence: 81%
“…The stopping power for a relatively low-Z absorber (Al) is about twice the one of a heavy target (Au). It has been shown that the range of ions in a highly heated absorber (plasma) is considerably shortened (Arnold & Meyer-ter-Vehn 1987), the effect amounting to a factor two already for a few eV temperature. However, the radiator is quickly disintegrated by the beam and the density may be considerably reduced during the heating process.…”
Section: Target Issuesmentioning
confidence: 99%
“…In ion beam driven inertial confinement fusion experiments [22][23][24][25] a high energy beam of ions deposits its energy in the target, causing the fuel inside to compress and to ignite through shock implosion. Two possible concepts are heavy ion beams [24,26] or light ion beams [23].…”
Section: Inertial Confinement Fusionmentioning
confidence: 99%
“…Two possible concepts are heavy ion beams [24,26] or light ion beams [23]. Profiles of density, temperature and pressure at different times are explained in depth by R.C.…”
Section: Inertial Confinement Fusionmentioning
confidence: 99%
See 1 more Smart Citation